Effect of particle cohesion on flow and separation in industrial vibrating screens. (April 2018) - Cleary, Paul W.; Wilson, Padarn; Sinnott, Matt D.
Highlights: The influence of cohesion on screen performance is investigated using DEM. For high cohesion the stickiness prevents proper flow through the machine. A rapid transition from sticky to processable occurs for intermediate cohesion. Flow is independent of the cohesion for low and medium cohesion levels. Particles collisions are sufficiently strong to allow percolation for BN < 0.1. Abstract: Screens are often used to separate large volumes of granular materials according to size. Discrete Element Method (DEM) modelling using non-spherical particle representations has previously provided increased understanding of the operation of such industrial screens operating both wet and dry. If a granular material has any combination of moderate amounts of water or clay present then it can become sticky which then affects its flow properties. We examine the influence of inter-particle cohesion on flow through and separation efficiency of such screens using a DEM model that includes a simple representation of the cohesive force. For high levels of cohesion the stickiness of the bulk material prevents proper flow through the machine with material building up in the rock box and then overflowing its back. For intermediate cohesion levels the material behaviour changes rapidly from sticky and difficult to flow to one for which particles can be properly processed by the screen. For lower cohesion levels the screen separation performance becomes independent of the level of cohesion level and behaves as if the material is cohesionless.